Factors influencing the knowledge parents/caregivers have about school-readiness for grade one scholars - Du Toit, Kirsten Jodi (My University, 2017)
This cross sectional quantitative study aimed to examine the understanding parents/caregivers have of school readiness requirements for Grade 1 children in comparison to expected scholastic criteria in the Gauteng province and the demographic factors which may affect this. A questionnaire was specifically designed for this study based on CAPS (Curriculum and Assessment Policy Statement) and IEB (Independent Education Board) and included looking at various area of development. Questionnaire content was validated by experts in a pilot study. Five hundred and ten questionnaires were circulated to parents/caregivers of Grade R and Grade 1 scholars in 2 urban and 1 private school. Two hundred and ten questionnaires were returned of which 180 were included in the data analysis. Overall results revealed that parents/caregivers had a better understanding of school readiness with respect to thinking and reasoning; motor ability; numerical skills and speaking abilities. They had moderate understanding of writing abilities; life skills and listening skills with the least knowledge about activities of daily living, reading and viewing skills and language structure and use. The only significant demographic factor that was identified was the level of education of the mother. This suggested that a higher level of education enabled the prediction of school readiness.
Research report submitted the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational therapy
Keywords: Caregivers Child, Preschool